Cloud Point Extraction Spectrophotometric Determination of Copper, Chromium and Cobalt by Salen as Reagent in Wastewater of Iraq - Ahmed Dhahir, Saadiyah; Rhajab Bakir, Sana (Asian Journal of Chemistry, 2014)
Cloud point extraction is a separation and preconcentration, simplicity, low cost, fast and environmental safety to determination of copper and cobalt by UV/visible spectrophotometry in some environmental samples such as wastewater of Rustimiyah city in Iraq and industrial sewage of Tannery Factories in Zafaraniyah, by using Salen as reagent in the presence of Triton X-100 (as a non-ionic surfactant) at lmax for copper 361 and for cobalt 378, 382 chromium. The optimum conditions for the cloud point extraction respect to several experimental parameters such as pH of the solution, Triton X-100 and Salen concentration incubation time, temperature and concentration of metals. The proposed method had a linear range for copper10-70 μg L-1 and for cobalt 10-70 μg L-1, chromium 10-70 μg L-1 the recovery of analytes was in the range, detection limits was 2.62, 2.19 and 0.5003 μg L-1 for for Cu = 0.9991, for Co = 0.9984, Cr = 0.9972 relative standard deviation (RSD) for Cu = 0.9108, Co = 0.9109 pH was equal to 10 for chromium, cobalt and 8 for copper.